Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

Speedup and efficiency of computational parallelization: A unifying approach and asymptotic analysis - Schryen, Guido (Journal of Parallel and Distributed Computing)

An early indicator for anomalous stock market performance - Fritz, Marlon; Gries, Thomas; Wiechers, Lukas (Quantitative Finance)
We propose an indicator for detecting anomalous stock market valuation in real time such that market participants receive timely signals so as to be able to take stabilizing action. Unlike existing approaches, our anomaly indicator introduces three methodological novelties. First, we use an endogenous, purely data-driven, nonparametric trend identification method to separate long-term market movements from more short-term ones. Second, we apply SETAR models that allow for asymmetric expansions and contractions around the long-term trend and find systematic stock price cycles. Third, we implement these findings in our indicator and conduct real-time market forecasts, which have so far been neglected in the literature. Applications of our indicator using monthly S&P 500 stock data from 1970 to the end of 2022 show that short-term anomalous market movements can be identified in real time up to one year ahead. We predict all major anomalies, including the 1987 Bubble and the initial phase of the Financial Crisis that began in 2007. In total, our anomaly indicator identifies more than 80% of all – even minor – anomalous episodes. Thus, smoothing market exaggerations through early signaling seems possible.
Keywords: General Economics; Econometrics and Finance; Finance

Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

A new mathematical formulation for the simultaneous optimization of charging infrastructure and vehicle schedules for electric bus systems - Stumpe, Miriam (Transportation Research Procedia)

Humans in XAI: Increased Reliance in Decision-Making Under Uncertainty by Using Explanation Strategies - Lammert, Olesja; Richter, Birte; Schütze, Christian; Thommes, Kirsten; Wrede, Britta (Frontiers in Behavioral Economics)

Moment or movement – the heterogeneous impact of the Black Lives Matter movement on personal and societal charitable crowdfunding campaigns - Seutter, Janina; Müller, Michelle; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (Internet Research)

Knowledge by Design in Education - Brase, Alexa Kristin; Jenert, Tobias (EDeR. Educational Design Research)
The editorial introduces the special issue Knowledge by Design in Education: Key challenges and experiences from research practice, posing key questions, offering an insight into ongoing discussions, and presenting an overview of the included articles.

Digitale Plattformen und Ökosysteme im B2B-Bereich - Fallstudien, Ansätze, Technologien und Tools
Das Herausgeberwerk präsentiert aktuelle Forschungsergebnisse und praktische Erkenntnisse aus dem Bereich von digitalen Plattformen und Ökosystemen im Business-to-Business-Kontext. Dabei liegt der Schwerpunkt auf empirischen und konzeptionellen Beiträgen. Neben Grundlagen, Enablern und Fallstudien werden ebenso mögliche Vorgehensweisen zur Entwicklung von Plattformen behandelt. Praktikerinnen und Praktiker aus den Bereichen Management, Strategische Planung und Business Development erhalten Impulse, um Digitale Plattformen und Ökosysteme erfolgreich voranzutreiben und so Potenziale innerhalb ihres Unternehmens zu realisieren. Forschende, Lehrende und Studierende aus den Bereichen Digitale Plattformen und Ökosysteme aus dem Business-to-Business-Kontext dienen die Beiträge als Anregung für intensive Diskussionen.